Morphological and biochemical analysis of hawthorn and rosehip of the Ulytau region - Mukan, Gauhar; Sankaibayeva, Anar; Kidarbek, Tannur; Baimaganbetova , Marzhan; Dostemessova, Anar (Fundamental and Experimental Biology, 2025)
The study investigates the morphological and biochemical profiles of two forms of Crataegus chlorocarpa and five forms of Rosa species (R. laxa, R. acicularis, R. spinosissima) from natural populations in the Zhanaarka district, Ulytau region, Kazakhstan. Geographical coordinates, shrub height, age, crown shape, yield, fruit size, color, and taste were assessed. Biochemical analyses quantified vitamin C, anthocyanins, leucoanthocyanidins, catechins, sugars, pectins, and titratable acidity using standardized methods. Rosa acicularis-058 showed the highest vitamin C content (576.4 mg/100 g FW), while Rosa spinosissima-064 ex[1]celled in anthocyanins (1259.3 mg/100 g FW). Crataegus forms were notable for their catechin content (up to 242.3 mg/100 g FW). Pearson’s correlation revealed strong positive correlations between vitamin C and leucoanthocyanidins (r=0.83, p=0.02), and between titratable acidity and sugars (r=0.86, p=0.01).UPGMA cluster analysis identified three distinct groups based on biochemical traits. These findings highlight the potential of these wild plants for nutraceutical development and breeding, as they surpass some conventional crops in bioactive compounds.